Cell Fate Determination of Lymphatic Endothelial Cells - Lee, Young Jae (Int J Mol Sci, 2020)
The lymphatic vasculature, along with the blood vasculature, is a vascular system in our body that plays important functions in fluid homeostasis, dietary fat uptake, and immune responses. Defects in the lymphatic system are associated with various diseases such as lymphedema, atherosclerosis, fibrosis, obesity, and inflammation. The first step in lymphangiogenesis is determining the cell fate of lymphatic endothelial cells. Several genes involved in this commitment step have been identified using animal models, including genetically modified mice. This review provides an overview of these genes in the mammalian system and related human diseases.